(untitled) (Hematology Meeting Reports, 2009)
In adults, follicular lymphoma (FL), characterized by a long clinical course with frequent relapses, accounts for up to one-third of cases of non-Hodgkin’s lymphoma. With the advent of newer treatment modalities therapeutic goals are shifting from improving quality of life to prolonging survival. Prognostic factors can help to determine the most effective treatment approach: aggressive treatment which may provide longer remission or softer treatment options that offer a more favorable tolerability profile. Chemotherapeutic regimens supplemented with additional treatment modalities, such as interferon therapy, appear to offer improved clinical and survival outcomes compared with chemotherapy alone. Chemotherapy followed by allogeneic bone marrow transplantation is associated with more favorable outcomes than autologous stem-cell transplantation but at the expense of higher treatment-related mortality rates. Immunotherapy, in the form of radiolabelled/nonradiolabelled monoclonal antibodies has provided new hope for the treatment of patients with FL. The addition of rituximab to chemotherapy has been shown to prolong time to treatment failure and time to progression as well as improving survival. Radioimmunotherapy with yttrium-90 (90Y)-ibritumomab tiuxetan and rituximab improves response rates in patients with relapsed or refractory FL without an increased risk of secondary malignancies. Data on the use of radioimmunotherapy strategies suggest that their use in combination with other treatment modalities can have a higher lymphoma-killing capacity. Whether or not this approach will translate into longer patient survival or a cure for a proportion of patients remains to be determined from ongoing randomized clinical trials.